Improving Proof Ability of Prospective Teachers with a Contextual Model on Trigonometry - Rahmad, Fajar Maulana; Qohar, Abd (Malikussaleh Journal of Mathematics Learning (MJML), 2020)
Proof ability of prospective teachers on Trigonometry material is still lacking. It can be seen when they carry out trigonometry proof that does not meet the proof indicators to conduct the research. This study aimed at improving proof ability of prospective teachers with a contextual model on Trigonometry materials. The research method used was classroom action research with the subjects of 30 students of Mathematics Education Study Program, State University of Malang, 2019. The research was conducted in two cycles by providing scaffolding action regarding proof steps, trigonometry identity scaffolding, and conflict cognitive of proof results. The research results showed that an increase of material indicator was 4%, an increase of completeness indicator was 24%, an increase of reason indicator was 59%, an increase of clarity indicator was 31%, an increase of conclusion indicator was 2%, and an increase of application capability indicator was 4% with a total increase of student’s ability was 23%.